Applications of Artificial Intelligence in Dermatology (International Journal of Food and Nutritional Sciences, 2022)
Artificial intelligence (AI) is becoming a more common research topic in medicine and is being used more frequently in dermatology. To assist direct and mould the future for medical care providers and recipients, it is necessary to comprehend how this technology is progressing. In order to assess the sorts of publications on the topic, the particular dermatological topics covered by AI, and the most difficult implementation barriers, we studied the literature. Only a few in-depth reviews exist despite the fact that numerous original articles and commentaries have been published to date. The majority of AI applications are concerned with identifying benign and malignant skin lesions, but there are also ones that deal with ulcers, inflammatory skin conditions, exposure to allergens, dermatopathology, and gene expression profiling. Applications frequently identify and analyse photographs, but there are also more and more tools available, such risk calculators. Despite the fact that many applications are technically feasible, significant implementation obstacles have been found, such as systematic biases, difficulties with standardisation, interpretability, and patient and physician acceptance. This evaluation sheds light on potential areas for and needs in future study. In dermatology, there is a critical need for clinical research that shows that the hurdles have been successfully overcome. With these objectives in mind, it's possible that AI will soon play a useful role in dermatology.